Bixu yangcheng geren weisheng xiguan
'Everybody must adopt hygienic habits.' Part of series "Thoroughly defeat the germ warfare of American imperialism. Everybody joins the patriotic hygienic campaign to prevent epidemics" (later slogan cropped from right side of poster). Printno. 0428.